Investigations of GaN growth on the sapphire substrate by MOCVD method with different AlN buffer deposition temperatures. (April 2016) - Huang, Wei-Ching; Chu, Chung-Ming; Wong, Yuen-Yee; Chen, Kai-Wei; Lin, Yen-Ku; Wu, Chia-Hsun; Lee, Wei-I; Chang, Edward-Yi
Abstract: The effects of different AlN buffer deposition temperatures on the GaN material properties grown on sapphire substrate was investigated. At relatively higher AlN buffer growth temperature, the surface morphology of subsequent grown GaN layer was decorated with island-like structure and revealed the mixed-polarity characteristics. In addition, the density of screw TD and leakage current in the GaN film was also increased. The occurrence of mixed-polarity GaN material result could be from unintentional nitridation of the sapphire substrate by ammonia (NH3 ) precursor at the beginning of the AlN buffer layer growth. By using two-step temperature growth process for the buffer layer, the unintentional nitridation could be effectively suppressed. The GaN film grown on this buffer layer exhibited a smooth surface, single polarity, high crystalline quality and high resistivity. AlGaN/GaN high electron-mobility transistor (HEMT) devices were also successfully fabricated by using the two-step AlN buffer layer.